Analisis Cara Kerja Sistem Deteksi Infeksi Worm Pada Komputer - Sumarno, Sumarno (METIK JURNAL, 2023)
Worms are a type of malware that has the ability to develop and spread automatically to other computers on a network without human interaction. This fast and undetectable infection capability makes worms a serious threat in the world of computer security. This research aims to explore the mechanisms and behavior of worm infection systems on computers. This study involves an in-depth analysis of the functions and methods used by worms to enter, infect, and exploit target computers. This researchalso explain how worms can cause damage to computer systems, steal confidential information, or even create botnet networks to carry out large-scale attacks. Research methods include collecting data from existing worm detection systems, analyzing system logs that occur, as well as simulations to understand how worms work in various scenarios. In addition, this research also consider protection and prevention techniques that can be used to protect computers and networks from worm attacks. Based on observations and experiments, the results of this research can be concluded that the worm infection system spreads through computers connected to the network or through other media on the network and does not require a certain moment to be a trigger to infect the target. It is hoped that the results of this research provide an in-depth understanding of worm infection systems on computers, allowing researchers and computer security practitioners to develop more effective protection strategies. Prevention and early detection efforts will be key in dealing with the growing threat from worms and similar types ofmalware.